Efektivitas Akun Instagram @kominfodiy Terhadap Penyebaran Informasi Publik Dalam Perspektif Islam - Sari, Rahmi Ikrima (IAINU Kebumen, 2022)
This study aims to analyze the effectiveness of Instagram social media and the forms of Instagram social media management on the dissemination of public information for government agency in Islamic perspective. This research was carried out on Instagram account owned by government agency in Yogyakarta, namely Communication and Informatics Office of DIY (Yogyakarta Special Region). The research method used was descriptive qualitative with data analysis technique using field notes and then data classification was carried out and arranged systematically according to indicators based on the results of the d ata analysis. The instruments used in this study were interview guidelines, data of Instagram posts, and documentation. The result of the research showed that the public information dissemination of Instagram account of @kominfodiy was categorized as effec tive in its use. The dissemination of public information carried out on @kominfodiy account, if related to Islamic perspective, is also regarded as effective based on the ethical values of Islamic communication, in accordance with those stated in the vers es of Quranic. In addition, the dissemination of information carried out by Communication and Informatics Office of DIY has also described good governance in